Elevated pulse pressure and cardiovascular risk associated in Spanish population attended in primary care: IBERICAN study - Moyá-Amengual, Ana; Ruiz-García, Antonio; Pallarés-Carratalá, Vicente; Serrano-Cumplido, Adalberto; Prieto-Díaz, Miguel Ángel; Segura-Fragoso, Antonio; Cinza-Sanjurjo, Sergio, the researchers of the IBERICAN study; García, Alfonso Barquilla; Rodríguez, Ángel Díaz; Cervantes, Carlos Escobar; Moreno, Francisco Javier Alonso; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction. Elevated pulse pressure (ePP) is an independent marker of cardiovascular risk (CVR) in people older than 60, and a functional marker of subclinical target organ damage (sTOD) which can predict cardiovascular events in patients with hypertension (HTN), regardless of sTOD. Objective. To evaluate the prevalence of ePP in adult population seen in primary care and its association with other vascular risk factors, sTOD and with cardiovascular disease (CVD). Materials and methods. Observational multicentre study conducted in Spain (8,066 patients, 54.5% women) from the prospective cohort study IBERICAN. Pulse pressure (PP) was defined as the difference between the systolic blood pressure (SBP) and the diastolic blood pressure (DBP). The ePP was defined as PP ≥60 mmHg. Crude and adjusted (for age and sex) ePP prevalence were determined. Univariate and multivariate analyses of the possible variables associated with ePP were carried out. Results. The mean of PP was 52.35 mmHg, and was significantly higher (p <0.001) in patients with HTN (56.58 mmHg) than in patients without HTN (48.45 mmHg). The prevalence of ePP adjusted for age and sex was 23.54% (25.40% men vs 21.75% women; p<0.0001). The prevalence of ePP increased linearly (R2= 0.979) with age, and was significantly more frequent in population aged ≥65 than in population aged <65 (45.47% vs 20.98%; p <0.001) and in patients with SBP/DBP ≥140/90 mmHg than in those with SBP/DBP <140/90 mmHg (64.66% vs 24.99%; p <0.001). HTN, left ventricular hypertrophy, low estimated glomerular filtration rate, alcohol consumption, abdominal obesity, and CVD were independently associated with ePP. 66.27% of patients with ePP had a high or very high CVR, as compared with 36.57% of patients without ePP (OR: 3.41 [95%CI 3.08-3.77]). Conclusions. Almost a quarter of the population had ePP, and its prevalence increased with age. The ePP was associated with an elevated CVR and was more frequent in men, patients with HTN, vascular risk factors and CVD. The ePP is a risk factor in the comprehensive assessment of vascular risk which must be early identified to optimize the diagnostic management and to establish the best therapeutic strategy in these risk groups.